Expertise and processing distorted structure in chess - Bartlett, James; Boggan, Amy L.; Krawczyk, Daniel C. (Frontiers in Human Neuroscience, 2013)
A classic finding in research on human expertise and knowledge is that of enhanced memory for stimuli in a domain of expertise as compared to either stimuli outside that domain, or within-domain stimuli that have been degraded or distorted in some way. However, we do not understand how experts process degradation or distortion of stimuli within the expert domain (e.g., a face with the eyes, nose, and mouth in the wrong positions, or a chessboard with pieces placed randomly). Focusing on the domain of chess, we present new fMRI evidence that when experts view such distorted/within-domain stimuli, they engage an active search for structure—a kind of exploratory chunking—that involves a component of a prefrontal-parietal network linked to consciousness, attention and working memory.